Determinants of intussusception in children under five years old visiting paediatric ward in selected hospitals of Sidama region Ethiopia - Abraham Fetene; Khaleel Nagarchi; Tamiru Getchew (Scientific Reports)
Abstract Intussusception is a significant cause of child mortality in sub-Saharan Africa, yet its exact causes remain unclear. Two main theories suggest it may be linked to dietary factors or infections, highlighting the need for research to identify specific risk factors. Accordingly, this study aimed to investigate the factors associated with intussusception in children under five years of age. A hospital-based unmatched case–control study design was employed, using an interviewer-administered structured questionnaire and a review of medical records for data collection. Data were analysed using SPSS version 25, and both bivariate and multivariable logistic regression models were applied. Variables with a p-value < 0.25 in the bivariate analysis were included in the multivariable logistic regression model. Statistical significance was declared at a p-value of less than 0.05. The study included 52 cases and 156 controls. The average age of the cases was 11.5 months (SD ± 8.60), and that of the controls was 18.9 months (SD ± 15.4). Among the participants, males accounted for 65.4% of the cases and 53.8% of the controls, while females comprised 34.6% of the cases and 46.2% of the controls. Variables significantly associated with intussusception included age between 6 and 12 months [AOR = 3.13; 95% CI: 1.04–9.41], history of gastrointestinal infections [AOR = 5.07; 95% CI: 2.14–11.9], mixed feeding with breast milk and formula [AOR = 17.12; 95% CI: 5.42–54], and feeding with breast milk and homemade foods [AOR = 9.28; 95% CI: 2.52–34.2]. This study demonstrates that children aged 6 to 12 months, a history of gastrointestinal infections, previous medication use, and mixed feeding practices (breast milk combined with formula or homemade foods) are associated with an increased risk of intussusception. Educating mothers and caregivers on proper hygiene practices to reduce infections, and promoting awareness of the benefits of exclusive breastfeeding, are essential preventive strategies.